The Influence of the Buddy reading Method Assisted with Flipbook Media on the Reading Abilty of Class V Students 3 Paraikatte - Nurfiana Nurfiana; Sulfasyah Sulfasyah; Tarman .A Arif (Edumaspul: Jurnal Pendidikan, 2024)
This research is an experimental study which aims to determine the effect of the buddy reading method assisted by flipbook media on the interest and reading comprehension ability of class V group 3 Paraikatte students. The Buddy Reading method which is supported by flipbook media has significant benefits in increasing the interest and reading comprehension skills of class V students. This method can be a fun form of learning so that it can increase students' interest in reading. The research carried out was experimental research using an experimental class and a control class. Data collection techniques through test instruments, questionnaires and observations to determine the increase in students' reading comprehension skills and reading interest through the buddy reading method. In the experimental group, the average reading interest was 70,784. Meanwhile, after treatment or giving the buddy reading method to the experimental group, the average interest in reading was 83,039. The same thing in the assessment of reading comprehension ability in the Pretest was 52.235. Meanwhile, the average reading comprehension ability on the Posttest was 84.235. On average, after treatment with the buddy reading method, the average reading ability in the experimental group was higher than the reading ability in the control group. The average reading ability in the experimental group was 84.235, which is higher than the average reading ability in the control group of 67.750.